Highly Dispersive Optical Solitons with Differential Group Delay for Kerr Law of Self-Phase Modulation by Sardar Sub-Equation Approach - Jawad, Anwar Ja’ afar Mohamad; Yildirim, Yakup; Biswas, Anjan; Ibraheem, Ibraheem Kasim; Alshomrani, Ali Saleh (Contemporary Mathematics, 2024)
The paper reports highly dispersive optical soliton solutions that are recovered with differential group delay with Kerr law of self-phase modulation. The Sardar’ s sub-equation approach is implemented for this retrieval. A full spectrum of optical solitons has been thus recovered. The parameter constraints are also displayed for the existence of such solitons.